2021
DOI: 10.1080/03007995.2021.1920901
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s disease exclusion diet in children with Crohn’s disease: a case series

Abstract: Exclusive enteral nutrition (EEN) represents an established, evidence-based dietary therapy used in Crohn's disease (CD); although successful, EEN is extremely restrictive with limited acceptability and prolonged use. The Crohn's disease exclusion diet (CDED) is a new, sustainable and patient-friendly dietary therapy used for the management of pediatric CD. CDED is designed to reduce exposure to dietary components hypothesized to negatively affect the microbiome, intestinal barrier and immunity. By focusing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…They found 28 (75.6%) of 37 and 14 (45.1%) of 31 children were in corticosteroid-free remission respectively, with a sustained reduction in serum level of C-reactive protein, fecal level of calprotectin and fecal Proteobacteria. CDED combined with PEN was also demonstrated to be effective on both induction and maintenance in children with mild-to-moderate CD by a case series [ 112 ]. In a multicenter randomized trial, 73 children with mild-to-moderate CD were given exclusive enteral nutrition or the CD exclusion diet (CDED) for 3 weeks.…”
Section: Dietary Strategies Alleviating Ibdmentioning
confidence: 99%
“…They found 28 (75.6%) of 37 and 14 (45.1%) of 31 children were in corticosteroid-free remission respectively, with a sustained reduction in serum level of C-reactive protein, fecal level of calprotectin and fecal Proteobacteria. CDED combined with PEN was also demonstrated to be effective on both induction and maintenance in children with mild-to-moderate CD by a case series [ 112 ]. In a multicenter randomized trial, 73 children with mild-to-moderate CD were given exclusive enteral nutrition or the CD exclusion diet (CDED) for 3 weeks.…”
Section: Dietary Strategies Alleviating Ibdmentioning
confidence: 99%
“…The impact of these diets on the pathogenesis and management of CD has already been thoroughly reviewed elsewhere [ 149 , 150 ]. Of special interest is the case of the CD exclusion diet (CDED, low in fat and animal protein with high content of carbohydrates and dietary fiber) [ 130 , 151 , 152 , 153 , 154 , 155 ], which is emerging as a potent alternative to EEN. It consists of three phases that start with a very restrictive diet supplemented with PEN, which is gradually reduced as new foods are introduced.…”
Section: Nutritional Strategies In CD Treatment and Managementmentioning
confidence: 99%
“…Clinical trials in pediatric patients with CD have shown that CDED plus PEN has comparable results in inducing remission. Furthermore, the patient’s compliance with an allowance to consume whole foods thereby increases the probability of success [ 154 ]. Anyway, all these studies have been focused on clinical outcomes and have disregarded data on the gut microbiome, which is why information on microbial changes associated with such diets is still scarce.…”
Section: Nutritional Strategies In CD Treatment and Managementmentioning
confidence: 99%
“…It has been recently shown that higher intakes of prebiotics and other beneficial foods, including fruits, vegetables, honey, oats, legumes, omega 3 fatty acids, and lean animal protein, increase SCFA-producing bacterial taxa abundances and reduce levels of inflammatory cytokines (e.g., interleukins IL-6/IL-8 and TNF-α) in adult patients with CD and UC [ 20 ]. The CD exclusion diet combined with partial enteral nutrition or the exclusive enteral nutrition (EEN), provided in a liquid, low-saturated-fat/heme/taurine and high-protein polymeric formula, are found to be effective nutritional therapies in inducing remission in children with CD [ 21 , 22 , 23 , 24 , 25 ]. However, the introduction of EEN therapy was found to decrease SCFA levels (including butyrate) and the α-diversity of SCFA-producing bacteria, with a lower abundance of Bifidobacterium , Bacteroides , Ruminicoccus , F.prausnitzii , and Blautia [ 21 , 26 , 27 , 28 ], which are thought to be associated with reduced gut inflammation in CD.…”
Section: Introductionmentioning
confidence: 99%